The relationship between firm mobility and tax level: Empirical evidence of fiscal competition between local governments - Fredrik Carlsen; Bjørg Langset; Jørn Rattsø (Statistics Norway, Research Department, 2005)
The mobility of the tax base may influence fiscal outcomes. The many theoretical contributions about the role of mobility are not matched by empirical evidence. Existing studies address strategic interaction between governments, but have little to say about mobility. We introduce a new measure of mobility conditions based on the geographic profit variability of industrial sectors. The econometric analysis shows a systematic negative relationship between mobility conditions and tax level among municipalities in Norway. The analysis takes into account neighborhood effects in a spatial model, and the endogeneity of mobility conditions is handled with instrumental variables.
Keywords: H71; H72; H73; C21; 330; Fiscal competition; mobility; local taxation